Pemberdayaan Kader Posyandu Dalam Pemenuhan Gizi Anak Usia Dini Berbasis Inovasi Olahan Produk Nugget Ayam Woli Di Desa Tembokrejo Kabupaten Banyuwangi - Alfaris Ilyas Agusta; Anisa Firdausiah; Dadi Sudrajat; Erik Dadang Kurniawan; Eris Wulandari; Faiz Mahardika; Inil Chukmu Ilalillah; Khilma Saidah; Muhammad Burhanuddin; Nurfadilatul Husna; Syaiful Bahri; Harvey Febrianta; Salvian Setyo Prayitno; Dani Agung Wicaksono (Jurnal Informasi Pengabdian Masyarakat, 2026)
This community service program aims to improve the knowledge and skills of Posyandu Community Health Volunteers in fulfilling early childhood nutritional needs through an innovative food product in the form of nuggets contain of chicken meat, carrot and broccoli. The activity was conducted in Tembokrejo Village targeting mothers with children aged 2–4 years. The methods used included counseling, hands-on training, and assistance in producing vegetable-based chicken nugget products. The implementation stages began with coordination with village authorities and the Posyandu Community Health Volunteers group, followed by the delivery of educational materials on the importance of vegetable consumption, demonstration of nugget production, and evaluation through pre-test and post-test. The results showed an increase in participants’ knowledge and skills in processing functional food, as well as a higher interest among mothers in providing healthy meals for their children. In addition, participants were able to independently practice the preparation of carrot and broccoli nuggets according to the provided procedures. The impact of this program includes increased community awareness regarding the importance of child nutrition, improved vegetable consumption among children through more appealing food innovations, and the emergence of opportunities for small-scale food-based entrepreneurship among Posyandu Community Health Volunteers member. This program is expected to serve as a sustainable community empowerment model in supporting food security and improving family nutritional quality.